Propuesta de un sistema de gestión ambiental para la finca bananera la fortuna en Arenillas - Rodríguez Cuenca, Juan Manuel (2015)
Today the competition is a full complement in the process of food chain and banana production is not an exemption, especially when it is the icon product of our country in exports of the same, so established to find a study to design a PROPOSAL FOR AN ENVIRONMENTAL MANAGEMENT SYSTEM FOR BANANA FARM "FORTUNE" IN ARENILLAS, for which they were established objectives and characterize the situation of the Hacienda "La Fortuna" during the years from 2009 to 2013, propose a methodology to audit were established on Current state of the Farm "The Fortune" and the academic community, considering the technical, legal, administrative, economic, environmental and community aspects, evaluate the results of the audits applied in the Farm "The Fortune" and propose a system Environmental Management for the Bank, which tribute to the sustained development of the academic community and the region in which it is nestled. Because the work was based on the following measurement variables: technical audit, Statutory audit, administrative audit, health and safety, community Audit and economic-financial audit, although being an estate of size about 20 ha, by its owners seek to improve to be able to maintain and the business of the production of banana fruit for export and helped to develop a number of monitoring different types of audit and thus leave a series of management plans which will enable them to remedy and improve driving conditions and development of staff and activities in the process of production and packing of fruit to see passed on in better overall satisfaction of both partners and harvesting field and customers, with better production and productivity hacienda as a company incorporated as such.